Coding polymorphisms of bone morphogenetic protein 2 contribute to the development of childhood IgA nephropathy - SUH, JIN-SOON (D.A. Spandidos, 2011)
Bone morphogenetic proteins (BMPs) are multi-functional growth factors belonging to the transforming growth factor β (TGFB) superfamily and are important in both preservation of kidney function and resistance to injury. BMP2 is highly regulated in the kidney, and high affinity binding sites for BMP2 have been identified in kidney epithelial cells. BMP2 has been demonstrated to play various roles in the pathogenesis of renal diseases. However, the role of the BMP2 gene in glomerulonephritis has not been previously investigated. We aimed to evaluate the association of BMP2 gene polymorphisms with immunoglobulin A nephropathy (IgAN) in children. We evaluated 187 pediatric patients with biopsy-confimed IgAN and 262 healthy controls. Two coding single nucleotide polymorphisms (cSNPs) in the BMP2 gene [rs235768 (missense, Arg190Ser) and rs1049007 (synonymous, Ser87Ser)] were selected and genotyped by direct sequencing. Genotypes of rs1049007 were associated with childhood IgAN in the codominant model II (GG vs. AA) [p=0.02; OR (95% CI), 0.16 (0.04–0.70)] and in the recessive model [p=0.0023; OR (95% CI), 0.16 (0.04–0.69)]. We also found an association between rs235768 and IgAN in the codominant model II (TT vs. AA) [p=0.01; OR (95% CI), 0.08 (0.01–0.57)] and in the recessive model [p=0.0002; OR (95% CI), 0.07 (0.01–0.55)]. After Bonferroni correction, these associations of rs235768 and rs1049007 with IgAN risk remained significant. In the haplotype analysis, the TG haplotype [p=0.01; OR (95% CI), 6.76 (1.55–29.50) in the dominant model] and AA haplotype [p=0.01; OR (95% CI), 0.08 (0.01–0.59) in the recessive model] showed associations with IgAN. The BMP2 gene may contribute to susceptibility to IgAN in Korean children.